Reading the Bible amid the Israeli-Palestinian conflict - Brueggemann, Walter (Theology today, 2016)
The Israeli-Palestinian conflict is a difficult, complex interface in which new postures, new possibilities, and new dangers are constantly emerging, so that reiterations of old formulae are at best unhelpful. A biblical interpreter can make only a very modest contribution to that ongoing urgent conversation. In what follows I will seek to sort out some of the extrapolations that are made from the Bible. It is clear that the Bible, as the rabbis have always understood, is filled with playful ambiguity and supple plural possibilities. Where that ambiguity and suppleness of the Bible is flattened into an ideological certitude that yields specific benefit, we likely have a misreading of the Bible.